EVALUASI SENSORI DAN ANALISIS USAHA KUKIS SUKUN PADAT GIZI - Widia Fitri; Netti Herawati; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of this research was to determine the level of preference panel and cookies descriptive characteristics and determine the feasibility business of cookies based breadfruit flour, tempe flour, rebon shrimp flour and red palm oil from its economic aspect. The treatments were TU1 (Tempe flour 20%, Rebon shrimp flour 1%), TU2 (Tempe flour 15%, Rebon shrimp flour 6%), TU3 (Tempe flour 10%, Rebon shrimp flour 11%) and TU4 (Tempe flour 5%, Rebon shrimp flour 16%).The treatments gave significant effect on descriptive test on attributes of color, shrimp aroma, salty flavor, shrimp flavor, tempe flavor and bitter end, as well as on the color attribute on the preferences test of adult panelists and the preferences test of child panelists.The best treatment on this research was TU1cookies, based on preference test of adult panelists and child panelists with consideration of the averages of ash content 1.87% has met quality standards cookies (SNI 01-2973-1992). TU1 cookies have moisture content 6,75%; protein content 13,87% andfat content 35,56%.The results of business analysis for one-time production with production scale 15 kg dough was that the business efficiency 1.37and thus the business of breadfruit cookies deserve to be established.   Keywords: Sensory evaluation, Business analysis, Breadfruit cookies